LEVERAGING DIGITAL HEALTH TECHNOLOGIES: ADMINISTRATIVE STRATEGIES FOR ENHANCING PUBLIC HEALTH OUTCOMES IN UNDERSERVED COMMUNITIES - JAN, MS; HAYAT, B; HUSSAIN, S; HUSSAIN, SI (Biological and Clinical Sciences Research Journal, 2024)
Integrating digital health technologies in public health systems has shown potential to enhance healthcare delivery, particularly in underserved communities. However, the differential impact of varying regional infrastructure and policies remains less explored. Objectives: This study investigates the impact of digital health technologies on improving public health outcomes in underserved communities. Methods: A mixed-methods study was conducted across three major cities in Punjab (Lahore, Faisalabad, and Multan), targeting underserved urban and rural populations. Three hundred healthcare administrators, policymakers, and digital health professionals from public and private healthcare settings participated. Data collection involved structured surveys, in-depth interviews, and focus groups. The geographical analysis assessed the variation in digital health adoption across different cities, factoring in urbanization levels and local infrastructure availability. The statistical analysis of the study variables was done using the SPSS 26 software, where multivariate regression analysis was conducted, and geographical mapping of health outcomes was also done. Results: Studies performed on the feedback revealed critical regional differences. In Lahore, which has an excellent urban setting and governmental policies covering telemedicine, the increase was 65% (p < 0. 01), while in Faisalabad and Multan, where internet facilities are not very strong and facing problems regarding funding, the increase was 50 and 45%, respectively. Reducing chronic disease management hospital readmissions was found to be 35% in Lahore and Faisalabad and 28% in Multan, signifying that digital health infrastructures influence patient outcomes. The administrative strategies, including policy changes, provider training, and other related programs, were found to have made quite a significant contribution, the contribution of which was estimated to be around 70%, the result being the coefficient of changes in the success of the implementation of the digital health notion (r = 0. 74, p < 0. 001). Conclusion: Lahore is also the beneficiary of digital health adoption, while the rural areas in Faisalabad and Multan need more investment in infrastructure and digital health literacy programs to realize comparable benefits.